2006
DOI: 10.1097/01.lgt.0000229564.11741.4e
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Melanoma of the Uterine Cervix

Abstract: Malignant melanoma is usually misdiagnosed specially in the chronic form. The immunohistochemical study is useful for definite diagnosis. Treatment is not well established, and the disease histogenesis has been controversial for a long time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Primary malignant melanoma of the cervix constitutes a rare disease,[4567] representing <2% of cases of malignant melanoma that affects the female genital tract. [4] Due to that the cervix is an unusual site for this type of neoplasm, the FIGO staging system for cervical cancer is used,[8] rather than the Clark and Breslow scales because the FIGO staging system correlates better with the prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary malignant melanoma of the cervix constitutes a rare disease,[4567] representing <2% of cases of malignant melanoma that affects the female genital tract. [4] Due to that the cervix is an unusual site for this type of neoplasm, the FIGO staging system for cervical cancer is used,[8] rather than the Clark and Breslow scales because the FIGO staging system correlates better with the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[1112] Adjuvant pelvic RT is considered in the case of positive surgical resection margins, when the parametrium is involved, or when lymph nodes are found to be involved. [4813] Adjuvant radiation may improve local control if the surgical margins are close.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no enough information about the real role of negative margins in primary melanoma of the cervix, the primary surgery should have the purpose of obtaining negative margins [7]; some authors recommend 2-cm margins as minimum [10,13]. The role of radiotherapy (RT) has not been well established, but it has been demonstrated that RT reduces the tumor size [4,9,11]. The use of adjuvant pelvic RT is considered in the case of not obtaining a satisfactory surgical resection margins, when the parametrium is involved, or when lymph nodes are found to be involved [7].…”
Section: Discussionmentioning
confidence: 99%
“…Age range varies from 20 to 78 years [7], being more common between 60 and 70 years [9]. Due to that the cervix is an unusual site for this type of neoplasm, the International Federation of Gynecology and Obstetrics (FIGO) staging system for cervical cancer is used [11], rather than the Clark and Breslow scales, because the FIGO staging system correlates better with the prognosis. Diagnosis of primary melanoma of the cervix entertains a high probability of being confused with another entity, due to the rarity of the disease [10].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no consensus on the therapeutic approach to follow [1, 2, 7]; in the reports found, initial treatment is referred of radical hysterectomy accompanied or not by radical pelvic lymphadectomy or superior vaginectomy [1, 2, 611]. …”
Section: Introductionmentioning
confidence: 99%